A Comparison of Fatigue Life Improvement Methods for an Existing Offshore Jacket Platform Structure - Reghu, Swethima; S, Sruthy (International Journal of Engineering and Technology, 2018)
Most offshore Jacket platforms are installed in shallow water, less than 300 meters for drilling and production of oil or gas. They are normally fixed to seabed and constructed as three dimensional frameworks with tubular members as structural elements. The surrounding environment around offshore platform is affected by various environmental loads that comprise of wind, waves, currents and earthquake. The major load in such structures is wave loading, repetitive in nature which causes time varying stresses that results global and or local fatigue damage on the offshore steel structure. This study includes fatigue assessment of a selected jacket structure using ANSYS software. This study concentrates mainly on the stress reduction at joints by various methods under the applied cyclic loading. The various methods considered in this study are providing: joint cans with branch stubs, grouted connections, FRP wrappings, stiffeners at the joint section. A comparison of various methods for reducing the hotspot stresses which increases fatigue life are studied and the most effective one is recommended.Â Â